Impact of Implementing Green Accounting and Capital Structure on Profitability - Al Hakim, Abdul Aziz; Wahyuningtyas, Endah Tri (Universitas Pamulang, 2024)
The Sri Kehati Index's financial performance increase between 2017 - 2020 is the driving force behind this study. This research suggests that companies that are members of the Sri-Kehati Index improve environmental performance in the face of environmental damage caused by companies, as evidenced by the increase in performance on the Sri-Kehati Index. This study aims to examine the impact of green accounting and capital structure on the profitability of the Indonesia Stock Exchange's Sri Kehati Index for the years 2017–2020. Environmental performance, costs, and disclosure are used to measure green accounting. The debt-to-equity ratio (DER) is used as an independent variable to measure capital structure, and return on assets (ROA) is used to measure profitability. Purposive sampling is the research method used; 11 companies make up the sample, which was chosen through a process called sample selection. Multiple linear regression analysis with a significance level of 0.05 is used in this study using SPSS version 26. The study's findings indicate that while environmental costs and the debt-to-equity ratio have a significant negative impact on profitability, environmental performance, and environmental disclosure have a positive and significant impact on profitability.